Membuka Potensi Kemitraan Komunitas dalam Mendorong Praktik Ekonomi Hijau: Pelajaran dari Kasus-kasus di Indonesia dalam Bidang Pertanian, Kehutanan, dan Pengelolaan Limbah: Unlocking the Power of Community Partnerships in Driving Green Economy Practices: Lessons from Indonesia’s Cases in Agriculture, Forestry, and Waste Management - Luh Kitty Katherina; Deshinta Vibriyanti; Inayah Hidayati; Vanda Ningrum (Society, 2023)
Amidst environmental challenges, natural calamities, poverty, and social disparities, the imperative to nurture sustainable practices that benefit the environment, economy, and society has grown more pronounced. The paradigm of green economics embodies efforts to elevate human well-being while upholding ecological sustainability. In the context of green economics within developing nations, the role of community practices becomes integral through the lens of community partnerships, which bolster community endeavors in achieving their objectives. Nevertheless, the lack of substantial empirical investigations into partnerships related to green economy practices remains conspicuous. This research aims to scrutinize community partnerships’ manifestations within the green economy practices domain. Utilizing a qualitative methodology, the study delves extensively into the practices encompassing organic coffee cultivation in Aceh, apiculture in West Sumatra, mangrove conservation in East Kalimantan, and waste management in Jakarta. Data collection involves in-depth interviews, direct observations, and focused group discussions within each locality, subjecting the data to thematic analysis. The study unveils several noteworthy findings. Firstly, community partnerships related to green economy practices emerge as collaborative endeavors that collectively empower communities to address economic and environmental challenges. Secondly, the configurations of community partnerships assume diverse forms, spanning from community-initiated efforts to those instigated by businesses or governmental entities. Thirdly, partnership engagements may involve a single community or extend to multiple communities within a region. Lastly, the research identifies establishing robust social institutions within communities as a foundational step toward executing community partnership endeavors that underpin green economic practices within Indonesian society. The social implications of this study furnish invaluable insights for the grassroots implementation of green economic practices. From an academic perspective, this research holds the potential to contribute to the evolution of partnership models within the realm of community development in the context of green economic activities.